Methods of applying nuclear simulation technology to the dynamic site testing of digital I&C system—I: Scheme of OLVT. (June 2017) - Li, Yankai; Lin, Meng; Yang, Zongwei; Hou, Yousheng; Yang, Yanhua
Highlights: Requirements and limitations of DCS site testing are clarified. A new structure design of OLVT to insert the simulator into the structure of DCS. Both the hard wire connection and soft network link are realized between simulator and DCS. OLVT is well accustomed to the conditions of DCS at site. Abstract: With a shift in technology to digital systems as the result of analog obsolescence and digital functional advantages, existing plants have begun to replace some current analog instrument and control (I&C) systems, while new plant designs fully incorporate digital systems. The requirements for dynamic site testing of digital distributed I&C system (DCS) come with the transitions from analog to digital technology because DCS have more complex structure (hardware/software/firmware), employ more complicated logic algorithms and have more dynamic interactions than the analog one. Further, the requirements are enhanced by the fact that there are several NPPs under construction each year in China, but a shortage of expert engineers and an urgency for continued construction. However, the dynamic testing methods developed for the design V&V or the factory testing cannot be applied directly in site testing because of the constraints of the conditions at site. In this paper, we generalized on-line virtual testing (OLVT) methods for site testing and expanded the application scope of OLVT to test a universal DCS system based on our experience and knowledge of site testing. An implementation scheme for OLVT is introduced to support flexible DCS-testing applications, including a structure design of OLVT, development of the DCS-testing platform and connection ways.